Job-pursuit intention in the FMCG Industry amid a pandemic: The rising importance of work-life benefits - Ang, Ann Kimberly Tiu (Animo Repository, 2021)
Grounded by the instrumental-symbolic framework of Kumari and Saini (2018), this research explored the drivers of job-pursuit intention in the fast-moving consumer goods industry amid the pandemic. The instrumental variables discussed in this study are career growth opportunities, work-life benefits, and compensation, while the symbolic attributes examined are corporate social responsibility and career-oriented social media. Other elements tackled in this study are fear of COVID-19, depression from COVID-19, and future career anxiety. A mixed-method approach of Creswell’s (2003) explanatory sequential design was used in this research. Whether a pandemic is occurring or not, findings have confirmed that job seekers are more likely to pursue a job when an employer is attractive, and has desirable career growth opportunities. However, the peri-pandemic study has interestingly shown a rising importance of work-life benefits for job seekers. It also highlighted how instrumental variables, namely compensation, work-life benefits, and career growth opportunities, should be appropriate and adequate to preserve the integral human development of job seekers. As for the symbolic variables, corporate social responsibility is not a statistically reliable predictor, while career-oriented social media does not moderate the effect of employer attractiveness on job-pursuit intention. Future research should be done to deepen insights by integrating new variables that emerged from the qualitative interviews with the instrumental-symbolic framework. They may also opt to test on a wider sample size with varying economic status. Thus, employers can focus on improving variables that will effectively acquire a more competitive pool of applicants.